Development And Characterization Of Moisture-Blown Natural Rubber Foam Prepared By Microwave Foaming Technique - Tan , Yizong (2013)

(untitled)
Investigation has been done on the feasibility of utilizing microwave radiation in foaming natural rubber. It was found that microwave foaming was able to foam natural rubber and the microwave processing is having advantages over both single and two-stage foaming process. Natural rubber is naturally non-polar and unsusceptible to microwave heating, but its behavior under the influence of microwave can be modified by incorporation of various additives. Foam with relative density as low as 0.14 can be produced with 8 pphr of azodicarbonamide (ADC) added, however signs of degradation can be observed when higher concentration of ADC was utilized. More interestingly, the moisture content in the rubber compound itself was able to act as a potential physical blowing agent with the aids of microwave radiation. Foam with the lowest relative density from this research, i.e. 0.10, was able to be produced by exploiting 1.25% moisture content in rubber compound. The successful foaming with moisture exceeded those foams formed with the addition of 10 pphr of azodicarbonamide. This would revolutionize the foam industry since water is a low cost, abundant and non-toxic material. The addition of fillers, silica and carbon black, will increase the susceptibility of rubber compound towards microwave heating, but in different manners. Silica will increase the polarity of rubber compound while carbon black increases the electrical conductivity of the compound. It was found that the addition of more than 10 pphr of both fillers ended up with unsuccessful production of natural rubber foam. For silica-added compound, the high viscosity of polymer melt available during foaming restricted the expansion of rubber matrix. In the case of carbon black added compound, the rapid rise in temperature under microwave radiation would burn and degrade the compound before the foam structure can be formed.